European governance: Common concerns vs. the challenge of diversity - Fritz W. Scharpf (Max Planck Institute for the Study of Societies, 2001)
The text is a comment on the White Paper on European Governance presented by the European Commission (COM[2001] 428, 25.7.2001). It begins by confronting the Commission's emphases with the governance problems that it fails to address, including the unresolved difficulties of economic-policy coordination among EMU member states, the adjustments of governance practices required by Eastern enlargement and, above all, the challenges implied by the fundamental shift of the European agenda - from the problems of achieving economic integration to the problems of coping with the consequences of economic integration. The primary proposals of the White Paper - reducing the involvement of the Council and the European Parliament in details of legislation and strengthening the role of the Commission at the expense of member states - would exceed the legitimacy of European institutions and they would also reduce the problem-solving capacity of European governance. European policy must be consensual if it is to be effective and legitimate. Hence it cannot short-circuit the efforts to achieve agreement among member states, even though it is increasingly confronted with problems for which uniform, Europe-wide solutions are not acceptable. Regrettably, the White Paper does not seem to be sufficiently interested in two modes of governance - closer cooperation and open coordination - that seem to have the potential for improving both the effectiveness and legitimacy of European policy in the face of continuing diversity. – – Der Text kommentiert das Weißbuch der Europäischen Kommission zu Fragen der European Governance (KOM[2001] 428, 25.7.2001). Eingangs werden die Vorschläge der Kommission den Problemen des europäischen Regierens gegenübergestellt, die das Weißbuch nicht behandelt. Dazu gehören u.a. die ungelösten Probleme der Koordination der nationalen Wirtschaftspolitik unter den Bedingungen der Währungsunion und die Probleme einer im Zuge der Osterweiterung erforderliche Differenzierung des europäischen Acquis. Vor allem aber fehlt jede Auseinandersetzung mit der grundlegenden Änderung der Anforderungen an die europäische Politik - von der Vollendung der wirtschaftlichen Integration zur Bewältigung ihrer Folgeprobleme. Die Vorschläge des Weißbuchs laufen darauf hinaus, die Rolle des Ministerrats und des Europäischen Parlaments auf die Festlegung von Grundsätzen zu beschränken und die Rolle der Kommission auf Kosten der Mitgliedstaaten wesentlich zu stärken. Eine Umsetzung dieser Vorschläge müßte jedoch die Grenzen der Legitimation der europäischen Institutionen überschreiten und zugleich die Problemlösungsfähigkeit der europäischen Politik vermindern. Die Union könnte die Suche nach einvernehmlichen Lösungen nicht aufgeben, ohne die Effektivität und Legitimität der europäischen Politik zu untergraben. Sie ist jedoch zunehmend mit Problemen konfrontiert, die nicht mehr durch einheitliche Regeln gelöst werden können. Aussichtsreich wären hier vielleicht zwei neuere Modalitäten der europäischen Politik - flexible Kooperation und offene Kooperation. Sie könnten die Erreichung gemeinsamer Ziele trotz heterogener Bedingungen in den Mitgliedstaaten erleichtern. Leider wird deren Potential im Weißbuch nicht ausreichend gewürdigt.
Keywords: 300